Modal analysis of transverse vibrations of a thin rectangular plate with a bonded piezoelectric patch - Tyagia A.; Ghoshb M.K. (My University, 2025)
Present problem deals with a rectangular plate with a PZT patch bonded to it. The plate is considered to be simply supported at its edges. Since PZT possess electromechanical properties, electrical properties along with mechanical properties are considered while deriving the equations of motion for transverse vibration of the plate with patch. The primary focus in this paper is how these electrical properties affect the plate behaviour in terms of transverse vibration frequencies. Transverse displacement has been represented by a double Fourier series. Open circuit boundary condition has been applied to the PZT patch. Results have been obtained for a plate covered fully by the patch and also for a plate covered partially by the patch. It has been found in the present investigation that electrical properties affect modal frequencies significantly. © 2011. MechAero Foundation for Technical Research & Education Excellence.